Pendidikan dan Pelatihan untuk Peningkatan Kompetensi Apoteker terkait Telefarmasi: Scoping Review - Permata Sari, Kartika Citra Dewi; Maria, Nisa; Kusumawardani, Larasati Arrum; Risni, Hindun Wilda; Syafhan, Nadia Farhanah; Fauziyyah, Afina Nur (Faculty of Pharmacy, Universitas Pancasila, 2023)
Antihypertensive and antidiabetic drugs in chronic kidney disease (CKD) patients undergoing hemodialyThe high demand for telepharmacy services led to the urge for proper training and education to enhance its quality. This review aimed to assess the implementation and outcomes of telepharmacy training and education programmes. This scoping review was conducted on ScienceDirect, Sage Journal, SpringerLink, and Google Scholar databases using keywords “training” OR “education” AND “telepharmacy,” “training” OR “education” AND “digital competency” AND “pharmacy.” Only English-written articles published between 2000 – 2023, original research and brief report were included in this review. Eight of 171 articles met the criteria and the study’s objectives. Those studies discussed telepharmacy learning programmes for pharmacy students in the USA (5 articles), UAE (2 articles), and Malaysia (1 article). The learning methods included didactic learning, case-based study, simulation/roleplay, and clerkship employing technological tools. Rubrics, quizzes, questionnaires, and objective structured clinical examination (OSCE) were used as assessment methods. All studies reported improved students’ knowledge, perceptions, and telepharmacy competencies. In conclusion, the telepharmacy learning programmes have effectively upgraded students’ knowledge and skills by various methods at every level. However, there remains a considerable need for evidence on suitable training for pharmacists to improve their telepharmacy competencies and service quality.